1998
DOI: 10.1111/j.1524-4725.1998.tb04271.x
|View full text |Cite
|
Sign up to set email alerts
|

Variable Venous Anatomy of the Popliteal Fossa Demonstrated by Duplex Scanning

Abstract: When SPJ incompetence is suspected, duplex scanning identifies the exact location of the junction and other associated pathology in the popliteal fossa, and allows the position of the junction to be marked on the leg preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 13 publications
0
19
0
1
Order By: Relevance
“…6 Most UK vascular surgeons (89% in a recent questionnaire study) employ routine diagnostic imaging before SSV surgery because of the difficulty assessing this area by hand-held Doppler, and the variable anatomy of veins in the popliteal fossa. 7,8 Preoperative duplex marking of the SPJ was done selectively, according to the result of the diagnostic scan by surgeons in the present study, as mirrored by national data. 9 As in other studies, preoperative duplex marking of the SPJ has not been shown to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…6 Most UK vascular surgeons (89% in a recent questionnaire study) employ routine diagnostic imaging before SSV surgery because of the difficulty assessing this area by hand-held Doppler, and the variable anatomy of veins in the popliteal fossa. 7,8 Preoperative duplex marking of the SPJ was done selectively, according to the result of the diagnostic scan by surgeons in the present study, as mirrored by national data. 9 As in other studies, preoperative duplex marking of the SPJ has not been shown to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] At the same time, SSV present a wide variability of anatomical junctions with the deep system: a fact that could influence its hemodynamics. 28 FV and PV belong to an intriguing anatomical site, whose valves' presence and location variability could represent a clue for this result explanation. 29,30 In fact, together with their anatomical variable distribution, valvular regions present potential confounding factors in the haemodynamics analysis, also due to the flow acceleration through the leaflets tract narrowing and to the valvular pockets turbulence.…”
Section: Discussionmentioning
confidence: 88%
“…Dilatation und/oderp athologische Strömungsumkehrd es Blutes (Reflux) in den Gastrocnemiusvenenk onnten vonm ehre-renA utoren in einemu nterschiedlichem Ausmaß bei Va rikosepatientensowohl mittels derP hlebographie (7,35), (farb)-duplex-sonographisch (1,2,4,6,9,21,22,33), alsa uchd urcha natomische Präparation (16) undi mR ahmenc hirurgischerI nterventionen(3, 17) festgestellt werden. Systematischev ergleichende funktionell-mor-phometrische Untersuchungen derV enae gastrocnemiae beie inemv enengesunden und venenkranken Kollektivb ezüglich der Anzahl der vorhandenenGastrocnemiusvenen, desVenenquerschnitts und derAnalyse derh ämodynamischen Situation liegen nicht vor.…”
Section: Résuméunclassified